A remarkable vision – Brewster's 1822 proposal for a 'National Burning Apparatus'. Issue 1 (2nd January 2016) - Spargo, P. E.
Abstract : In order to reduce the energy losses resulting from the thickness of large burning glasses, the French naturalist the Comte de Buffon proposed that such lenses should consist of a relatively small central lens surrounded by a series of stepped annular glass rings, all ground to direct light to the same focal point. In order to simplify the problems associated with manufacturing such rings, the Scottish physicist Sir David Brewster suggested in 1822 that it would be simpler if each annular ring consisted of a number of separate close-fitting segments. Convinced of the importance for scientific research in Britain of the availability of a burning glass larger than could be afforded by any single institution, he proposed the construction of a 'National Burning Apparatus, ' "to the construction of which all the scientific institutions in the kingdom might contribute" – a remarkably prescient vision of the need for and value of national research facilities. He also outlined some of the important research that might be undertaken using such a device. However, his proposal elicited no response.